Propuesta de un sistema de manejo de residuos hospitalarios en los centros de salud pública del cantón Buena Fé - Martínez Chévez, Víctor Francisco (2015)
Hospital wastes are all residues generated in hospitals, clinics, laboratories, offices and generally in all health care centers. Due to the infectious nature of some of these present, it is important to know the risk they may have for health and the environment if not handled properly and responsibly. That is why the present study was aimed to develop a proposal on the management of hospital waste in public health centers canton Buena Fe, to raise awareness of environmental conservation, reduce infectious waste, reuse ordinary waste of different areas of health and of handling all hazardous waste generated. In a first stage was carried out a diagnosis of the current situation of the management of hospital waste, where was visited and observed the different public health centers Canton Buena Fe was performed, they worked with surveys Likert to determine if it complies with environmental legislation and health regulations. The results demonstrated poor knowledge in the management and treatment of hospital waste from generation to disposal thereof, causing a breach of the laws, regulations, rules and legal bodies of the country. Finally, according to different variables analyzed with different outcomes a management plan for waste of public health centers Canton Buena Fe is proposed, referring to the different treatments to be used is made for each of the phases of hospital waste and the various options for treatment before being disposed in municipal waste dumps.